Indonesian Junior High School Students’ Problem in Learning EFL - Faiz Maransha Andrean; Ernati Ernati (Innovative: Journal Of Social Science Research, 2023)
The purpose of this study was to determine whether students face difficulties in learning English. The study involved 168 students from the 7th grade at SMPN 2 Sawahlunto, located in the West Sumatra Province. A questionnaire was used as the instrument for this descriptive study, which revealed two aspects of English learning problems. The reliability of the questionnaire was assessed using Cronbach's alpha, resulting in a high reliability coefficient of 0.73. The data was categorized as either having or not having a problem based on the criterion of ≥ M and < M, respectively. The findings indicated that 88 students (52%) encountered problems in learning English, while 80 students (48%) did not. Therefore, it can be concluded that 7th-grade students are experiencing difficulties in learning English, primarily due to external factors. This study suggests that school leaders, teachers, and future researchers should collaborate to address and alleviate these problems faced by the students.